Influence of smoking on colonic gene expression profile in Crohn's disease. - Ole Haagen Nielsen (PLoS ONE, 2009)
BACKGROUND: The development and course of Crohn's disease (CD) is related to both genetic and environmental factors. Smoking has been found to exacerbate the course of CD by increasing the risk of developing fistulas and strictures as well as the need for surgery, possibly because of an interaction between smoking or nicotine on macrophage function and the intestinal microvasculature. Several genes are involved in the pathogenesis of CD, and in this study the gene expression differences of the descending colonic mucosa were investigated in CD (smokers or never smokers) and controls (smokers or never smokers). AIM: To identify any difference in gene expression of the descending colonic mucosa between smoking and never-smoking CD patients (and controls) by determining genetic expression profiles from microarray analysis. METHODS: Fifty-seven specimens were obtained by routine colonoscopy from the included material: CD smokers (n = 28) or never-smokers (n = 14) as compared to fifteen healthy controls (8 smokers and 7 never-smokers). RNA was isolated and gene expression assessed with Affymetrix GeneChip Human Genome U133 Plus 2.0. Data were analyzed by principal component analysis (PCA), Wilcoxon rank sum test and multiple linear regressions. Real-time (RT) PCR was subsequently applied to verify microarray results. RESULTS: The PCA analysis showed no intrinsic clustering of smokers versus never-smokers. However, when Wilcoxon rank sum test corrected with Q values were performed, six known genes were significantly expressed differently in the inflamed CD smokers as compared to the inflamed CD never-smokers: ring finger protein 138 (RNF138), metalothionein 2A (MT2A) and six transmembrane epithelial antigen of the prostate 3 (STEAP3), SA hypertension-associated homolog, PGM2L1 and KCNJ2. The subsequent RT-PCR-analyses verified, however, that only RNF138, MT2A and STEAP3 were significantly up-regulated in CD smokers in specimens with inflammatory activity of the descending colon. CONCLUSIONS: The present study demonstrates that the genes, RNF138, MT2A, and STEAP3 are differently expressed in the inflamed descending colon of smoking versus never-smoking CD patients, which might be of relevance for the poorer clinical course among CD smokers. Many gastroenterologists are still not totally aware of the benefits of smoking cessation in relation to CD, and do not put much effort into getting the patients to quit, therefore more information on the negative effects of smoking, seems warranted.